An Exploratory Double-Blind Study of Caffeine Effects on Performance and Perceived Exertion in Judo. Issue 3 (June 2019) - Saldanha da Silva Athayde, Marina; Kons, Rafael L.; Detanico, Daniele
This study analyzed the effects of caffeine ingestion during judo matches on judo athletes' match-derived performance and perceived exertion responses. We applied a double-blind randomized crossover (caffeine vs. placebo conditions) research design. Twelve male athletes performed three 5-minute matches separated by 15 minutes of passive rest. Immediately after each match, the athletes completed ratings of perceived exertion (RPEs), and one minute before beginning the second and third matches, they provided ratings of perceived recovery (RPRs). We filmed all matches for subsequent analysis of the athletes' technical skills. We found no interaction between condition and time of RPE, RPR, and match-derived technical variables, but number of attacks and RPR decreased over the matches, and RPE increased in both conditions. Three participants showed individual positive responses to caffeine ingestion for number of attacks. Attacks, efficiency, and effectiveness presented low sensitivity in both conditions, as only large changes could be identified. We conclude that caffeine ingestion did not provoke changes in either perceived exertion or match-derived performance. Match-derived technical variables were not sensitive for detecting small or medium effects of caffeine, but perceived exertion may detect at least medium effect after caffeine ingestion.